(untitled) (Research, Society and Development, 2021)
Arboviruses are classified as a group of pathologies caused by denominated arbovirus, in particular Aedes aegypti. In the national scenario, the ones that gain more prominence are Dengue, Yellow fever, Chikungunya and Zika. The aim of this study is to describe the main clinical problems resulting from arboviruses through a literature review. The article follows the precepts of the exploratory study, through a bibliographic research, which is developed from material already elaborated and disseminated in databases. The analyzed texts showed similarities between the symptoms of the 4 arboviruses studied in mild or initial cases, as well as the uniqueness of the clinical conditions of each of these diseases. Recent research brings a new understanding of the symptoms and their possible repercussions to the body, as well as new possibilities for treatment and subsequent appropriate follow-up to the patient. Monitoring the patient’s evolution as well as a good understanding of aggravating signs are vital for containing potential clinical problems. In addition, the injuries observed end up developing socioeconomic impact factors, due to the great damage in the maintenance of the production chain and the weakening of patients.